Custom-made approach to a patient with post-burn breast deformity - Bayram, Yalcin (Medknow Publications & Media Pvt Ltd, 2014)
Second and third degree burns on breasts at preadolescent period may cause severe breast deformations. This deformation can be variable depending on severity and location of the burns, personal adolescent patterns, and treatment modality in acute burn period. A 21 year old female patient admitted to our department for her breast deformation due to burn contracture at the inferior pole of the right breast. On physical examination we defined that development of the volume of the right breast was equal to the left, and inferior pole of the right breast was flattened due to contracture, and nipple was projected to inferior. We found that inframammary crease of the right breast was 2 cm lower than that of left; andthe distance of nipple-inframamary crease was 4.7 cm while areola-inframmary crease was 2 cm. New nipple-areola complex level was identified according to left breast's level. Medial and lateral lines were planned to merge inferiorly at 2 cm above inframmary crease in a plan similar to vertical mammaplasty. Superior pedicle carrying nipple areola was desepitelised. Lower parenchymal V flap was transposed superiorly and attached to the pectoral muscle. Inferior parts of the lateral and medial glandular flaps were excised to form new inframammary crease. The desired laxity of skin at the lower pole was obtained by performing a new Z- plasty between lateral and medial skin flaps. Breast symmetry was confirmed by postoperative objective measurements between left and right breasts. Patient's satisfaction and aesthetic appearance levels were high. Breasts deformation patterns caused by burns, trauma and mass exsicion due to cancer could not be addressed with traditional defined techniques. Special deformations can be corrected by custom made plannings as we presented here.